The nexuses between energy investments, technological innovations, emission taxes, and carbon emissions in China - Ma, Qiang; Murshed, Muntasir; Khan, Zeeshan (Energy policy, 2021)
This paper aims to analyze the impacts of emission taxes, investments in the energy sector, expenditure on research and development, technological innovation, and tertiary sector development on the Chinese provincial carbon dioxide emission figures between 1995 and 2019. The econometric analysis involved the application of the latest methods which can simultaneously account for cross-sectional dependency, slope heterogeneity, and structural break issues in the data. The overall findings revealed that provincial growth and tertiary sector development were responsible for the aggravation of the carbon dioxide emission trends in China. In contrast, higher energy investments, technological innovation, renewable energy use, expenditure on research and development, and carbon emission taxes are found to abate carbon dioxide emissions and, therefore, facilitate the carbon-abatement agenda of China. Besides, the findings also revealed emission taxes, investment in research and development, technological innovation, and renewable energy use jointly reduce carbon dioxide emissions further. In line with these abovementioned findings, several policy-level recommendations are put forward. •The macroeconomic determinants of China's carbon-neutrality target are examined.•Energy investment, technological innovation, and renewable energy reduce CO2.•R&D expenditure and emission taxes reduce CO2.•Provincial growth and tertiary sector development boost CO2.•R&D expenditure, Renewable energy and technological innovation jointly reduce CO2.